Governance and Urban Changes in the Financialized Post-crash Period. (May 2020) - Quintana, Francisco
In this article, we examine the fundamentals of the changes that have taken place in governance and urban spaces after the crisis-recession of 2007–2009, post-crash. In this investigation, we focus on the shifts that have occurred, mainly in the US and the European Union. However, given the existence of global/local asymmetric economic and political interrelations, many of these observations can be extrapolated to other territories, including Canada, Asian countries and Latin America. In particular, these transformations are essential ingredients of the systems of governance and new economic strategies of the Tradable Income-Yielding Asset (TIYA) matrix for the refinancing and structuring of planetary urbanization and, in general, of the processes for accumulation of capital. In order to carry out this analysis, we have divided the text into three parts: 1) governance post-crash; 2) urban spaces and financial recovery; and 3) conclusion.